(untitled) (Journal of Science and Technology, 2016)
Oxisoils (or Ferralsols) have been recognized in the High Rain Forest (HRF) agro-ecological zone of Ghana. There is no documented information about these soils in the Moist Semi- Deciduous Forest (MSDF) agro-ecological zone of Ghana where climatic conditions conducive for Oxisol formation have been identified in parts of the zone. The paper seeks to establish the development of Oxisols or Ferralsols in parts of the MSDF so that appropriate management practices can be adopted for their sustainable use in the zone. Nine soil profiles were dug, de- scribed and sampled along a transect running from the HRF to MSDF zones of Ghana. Four of the profiles were located in the HRF and five in the MSDF. The HRF soils are Ninisu, Ankasa, Boi and Bremang series, while Wacri, Kukurantumi, Bekwai, Nzima and Kokofu series are the MSDF soils. Using rainfall and evapotranspiration data, morphological and easily measurable physico-chemical properties in the laboratory, the soils were evaluated for the development of Oxisols in the two agro-ecological zones in Ghana. These properties were also used to classify the soils into the Soil Taxonomy, world Reference Base for Soil Resources (WRB) and the Ghana Soil Classification Systems. Rainfall is higher in the HRF than MSDF. However, evapotranspiration distribution is similar in the two zones. Munsell hue is less variable in the HRF than the MSDF. This indicates greater moisture variability in the MSDF compared to the HRF. All the soils in the HRF and two in the MSDF (Wacri and Kukurantumi series) show pseudosand structure in the subsoil, which is characteristic with Oxisols (or Ferralsols). Though the soils are highly weathered with ECEC values being <12 cmol(+)/kg soil, the inten- sity is greater with the HRF soils. Silt:clay ratios are <0.7 in the subsoils of the HRF soils com- pared to those of the MSDF. CEC:clay are mostly <0.3 in all the soils, indicating kaolinitic clay mineralogy. Under the Soil Taxonomy system, all the HRF soils and two in the MSDF (Wacri and Kukurantumi series) are Oxisols. The remaining three MSDF soils are Ultisols. The Ox- isols classify as Ferralsols and the Ultisols, Acrisols in the WRB. This preliminary assessment shows that Oxisosl (or Ferralsols) also occur in the MSDF under udic moisture regimes. This is important for soil management in the MSDF.